The Bad Seed goes to the library - John, Jory; Oswald, Pete; Joshaghani, Saba (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2022)
"The bad seed is in a good mood...for once. That's because there's a really cool book at the library available for checkout. The bad seed reads, and reads, until the book can't be read anymore. But suddenly, he gets bad news: The book must be returned to the library so another seed can enjoy it. Will the bad seed return to his baaaaaad ways and keep the book?"--
Ages 4-8.
Guided reading level K.
Keywords: Seeds -- Juvenile fiction; Books and reading -- Juvenile fiction; Libraries -- Juvenile fiction; Courtesy -- Juvenile fiction; Etiquette -- Juvenile fiction; Conduct of life -- Juvenile fiction; Seeds -- Fiction; Books and reading -- Fiction; Libraries -- Fiction; Courtesy -- Fiction; Etiquette -- Fiction; Conduct of life -- Fiction; Semences -- Romans, nouvelles, etc. pour la jeunesse; Livres et lecture -- Romans, nouvelles, etc. pour la jeunesse; Bibliothèques -- Romans, nouvelles, etc. pour la jeunesse; Morale pratique -- Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / Books & Libraries; JUVENILE FICTION / Social Themes / Values & Virtues; JUVENILE FICTION / Readers / Beginner; Books and reading; Conduct of life; Courtesy; Etiquette; Libraries; Seeds; Seeds -- Juvenile fiction; Libraries -- Juvenile fiction; Courtesy -- Juvenile fiction; Etiquette -- Juvenile fiction; Seeds -- Fiction; Libraries -- Fiction; Courtesy -- Fiction; Etiquette -- Fiction; Humorous fiction; Children's stories; readers; Fiction; Humorous fiction; Juvenile works; Humorous fiction; Readers (Publications); Independent readers; Lectures et morceaux choisis